Синтез координаційних сполук деяких d-металів та ураніл-іона з 5-(4-піридил)-1,2,4-триазол-α-ілоцтовою кислотою та її амідом - Хоменко, Д.М.; Дорощук, Р.О.; Лампека, Р.Д. (Видавничий дім "Академперіодика" НАН України, 2008)
A new method of preparation of 5-(4-pyridyl)-1,2,4-triazol-α-ylacetic acid and its amide is developed. Eight new coordination compounds containing these ligands are synthesized. All obtained complexes are studied by means of CHN analysis and IR-spectroscopy. In addition, NMR(¹H) spectra of coordination compounds with diamagnetic metals are obtained.